Konsep Memadu Cinta dalam Pernikahan: Studi Kritik Hadis - Vedu Pamungkas Putra; Multi Saridewi; Wawan Hernawan (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the concept of making love in the hadith about marriage. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith criticism, while the material object is the hadith about marriage in the history of Ibn Majah No. 1837. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi that meets the qualifications of maqbul ma'mul bih for the practice of Islam about the concept of combining love in marriage. This study concludes that the hadith narrated by Ibn Majah no. 1837 is relevant to be used as the basis for the concept of combining love in marriage, that in marriage there is the essence of love in its truest sense.